Identification of lncRNAs by RNA Sequencing Analysis During in Vivo Pre-Implantation Developmental Transformation in the Goat - Ling, Ying-hui; Zheng, Qi; Li, Yun-sheng; Sui, Meng-hua; Wu, Hao; Zhang, Yun-hai; Chu, Ming-xing; Ma, Yue-hui; Fang, Fu-gui; Xu, Li-na (Frontiers in Genetics, 2019)
Pre-implantation embryonic development is a dynamic, complex and precisely regulated process that is critical for mammalian development. There is currently no description of the role of the lncRNAs during the pre-implantation embryo stages in the goat. The in vivo transcriptomes of oocytes (n=3) and early embryos (n=19) at seven developmental stages in the goat were analyzed by RNA sequencing (RNA-Seq). The major zygotic gene activation (ZGA) event was found to occur between the 8- and 16-cell stages in the pre-implantation embryos. We identified 5160 differentially expressed lncRNAs (DELs) in developmental stage comparisons and functional analyses of the major and minor ZGAs. Fourteen lncRNA modules were found corresponding to specific pre-implantation developmental stages by weighted gene co-expression network analysis (WGCNA). And a comprehensive analysis of the lncRNAs at each developmental transition of high correlation modules was done. We also identified lncRNA-mRNA networks and hub-lncRNAs for the high correlation modules at each stage. The extensive association of lncRNA target genes with other embryonic genes suggests an important regulatory role for lncRNAs in embryonic development. These data will facilitate further exploration of the role of lncRNAs in the developmental transformation of pre-implantation stage embryos.